2015
DOI: 10.1007/s12020-015-0681-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of anthropometric and metabolic parameters, and quality of life following treatment with dual-release hydrocortisone in patients with Addison’s disease

Abstract: Disclosure statement: The Authors have nothing to disclose. 2Abstract Purpose: In patients with Addison's disease (AD), a dual-release preparation of hydrocortisone (Plenadren, PLEN) has been demonstrated to maintain cortisol levels in a more physiological range than conventional glucocorticoid therapy, and to exert positive effects. This study aimed to assess variations of anthropometric, metabolic and hormonal parameters in patients with AD after switching from conventional hydrocortisone (HC) treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 31 publications
(29 reference statements)
6
85
3
3
Order By: Relevance
“…In addition, positive changes were also evident in a three-week walking programme reported in the study of GoldhaberFiebert et al although insignificantly small. 48,49 The percentage decline in LDL-C (11.9%) observed in this study is greater than the value in the meta-analysis conducted by Kelly and Kelly which indicated a significant reduction by 5% for LDL-C. 50 The improvement in TC, T, HDL-C-C and LDL-C exhibits clear evidence of reduction in atherogenic traits of risk factors 51,52 and better quality of life [53][54][55] of the sample studied. Authors observed that there are variations in the findings associated with this study in literature which are attributed to intensity, duration and frequency of exercise trainings and sample sizes.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, positive changes were also evident in a three-week walking programme reported in the study of GoldhaberFiebert et al although insignificantly small. 48,49 The percentage decline in LDL-C (11.9%) observed in this study is greater than the value in the meta-analysis conducted by Kelly and Kelly which indicated a significant reduction by 5% for LDL-C. 50 The improvement in TC, T, HDL-C-C and LDL-C exhibits clear evidence of reduction in atherogenic traits of risk factors 51,52 and better quality of life [53][54][55] of the sample studied. Authors observed that there are variations in the findings associated with this study in literature which are attributed to intensity, duration and frequency of exercise trainings and sample sizes.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, advantages other than patient convenience have not been robustly demonstrated to date. However, data are steadily accumulating to support improved metabolic outcomes 31,32 and the use of Plenadren® is likely to increase. An additional product, Chronocort®, containing microparticulate hydrocortisone with delayed absorption, is also currently in development.…”
Section: New Developmentsmentioning
confidence: 99%
“…Recently, the disease-specific questionnaire AddiQoL was developed (40) and validated (41) as an evaluative tool in PAI, which might facilitate the detection of minor changes in well-being in future clinical trials and during routine follow-up of patients (42,43,44,45).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%